2013
DOI: 10.1128/jb.00859-13
|View full text |Cite
|
Sign up to set email alerts
|

A Zn-Dependent Metallopeptidase Is Responsible for Sensitivity to LsbB, a Class II Leaderless Bacteriocin of Lactococcus lactis subsp. lactis BGMN1-5

Abstract: e Lactococcus lactis subsp. lactis BGMN1-5 produces a leaderless class II bacteriocin called LsbB. To identify the receptor for LsbB, a cosmid library of the LsbB-sensitive strain BGMN1-596 was constructed. About 150 cosmid clones were individually isolated and transferred to LsbB-resistant mutants of BGMN1-596. Cosmid pAZILcos/MN2, carrying a 40-kb insert, was found to restore LsbB sensitivity in LsbB-resistant mutants. Further subcloning revealed that a 1.9-kb fragment, containing only one open reading frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 27 publications
0
51
0
2
Order By: Relevance
“…The Receptor Binding Domain of LsbB Is Located in the C-terminal Half-It has recently been shown that LsbB requires the membrane-bound protease YvjB as a receptor on target cells (18). Given that the structure of LsbB revealed distinct domains within the molecule, we wished to examine which part of LsbB is involved in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Receptor Binding Domain of LsbB Is Located in the C-terminal Half-It has recently been shown that LsbB requires the membrane-bound protease YvjB as a receptor on target cells (18). Given that the structure of LsbB revealed distinct domains within the molecule, we wished to examine which part of LsbB is involved in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…Recently a zinc-dependent membranebound metallopeptidase has been identified as the receptor for LsbB on target cells (18). In the present work, we determined the three-dimensional structure of LsbB and defined the part of the bacteriocin involved in the receptor binding.…”
mentioning
confidence: 99%
“…Se observan fluctuaciones en los niveles de proteína en el medio, el consumo de proteína muestra incrementos en algunos de los tiempos de evolución, este tipo de comportamiento puede ser la respuesta a la utilización de la proteína del medio y su posterior uso en el construcción de sustancias peptídicas como son la bacteriocinas [42].…”
Section: Consumo De Proteínasunclassified
“…A maltose-ABC transporter was found to be required in target cells for sensitivity to garvicin ML, a circular bacteriocin (class IIc) (15). By screening of a cosmid library and genome sequencing of resistant mutants, a Zn-dependent metallopeptidase was found to be the target for the LsbB (class IId) and related bacteriocins (16). In addition, UppP has been found to be the bacteriocin receptor for lactococcin G and enterocin 1071 (both class IIb) (17).…”
mentioning
confidence: 99%
“…It has a narrow inhibitory spectrum containing mostly lactococcal strains. The target receptor for LsbB is YvjB, a member of the highly conserved Zn-dependent membrane-located protease M50 protein family (16). Some members of this protein family are known to be involved in gene regulation in response to stress in Escherichia coli and Enterococcus faecalis (19)(20)(21)(22).…”
mentioning
confidence: 99%